Giving Diligence Its Due: Accessing Digital Images in Indigenous Repatriation Efforts - Susan Douglas; Melanie Hayes (Heritage, 2019)
An increasing volume of images is available online, but barriers such as digital locks, proprietary interests and narrow scope of information uploaded to image databases maintain structures that have impeded repatriation efforts in the real world. Images of objects (cultural material) in the digital environment support cultural heritage. Institutions are developing complex solutions relevant in the network environment to further repatriation initiatives. These solutions facilitate discovery, opening avenues for research into the ethics of ownership that cross the physical/digital divide. There have been calls for strengthening the potential for use of pertinent information in order to protect and recover cultural heritage through increased visibility. However, some museums still limit access to images. We examine the issues and their implications referencing case studies specific to Indigenous, Inuit and Métis peoples of Canada.